Multidisciplinary Consensus Guideline for Managing Trigger Finger: Results From the European HANDGUIDE Study. Issue 10 (1st October 2014) - Huisstede, Bionka M.A.; Hoogvliet, Peter; Coert, J. Henk; Fridén, Jan; ,
Abstract : Background: Trigger finger is characterized by sometimes painful snapping or locking when flexing the finger. Although trigger finger is frequently seen in clinical practice, no standard treatment protocol has been established as "best practice." Objective: The aim of this study was to achieve consensus on a multidisciplinary treatment guideline for trigger finger. Design: A European Delphi consensus strategy was initiated. Systematic reviews reporting on the effectiveness of surgical and nonsurgical interventions were conducted and used as an evidence-based starting point for this study. Setting: In total, 35 experts (hand therapists and hand surgeons selected by the national member associations of their European federations and physical medicine and rehabilitation physicians) participated in the Delphi consensus strategy. Measurements: Each Delphi round consisted of a questionnaire, an analysis, and a feedback report. Results: After 4 Delphi rounds, consensus was achieved on the description, symptoms, and diagnosis of trigger finger. The experts agreed that use of orthoses (splinting), corticosteroid injections, corticosteroid injections plus use of orthoses, and surgery are suitable treatment options. Relevant details for the use of orthoses, corticosteroid injections, and surgery were described. Main factors for selecting one of these treatment options were identified as severity and duration of the disease and previous treatments received. A relationship between the severity and duration of the disorder and the choice of therapy was indicated by the experts and reported on in the guideline. Limitations: The results represent a group's opinion at a given point in time. When the evidence for the effectiveness of interventions increases, experts' opinions will change, and the guideline should be re-evaluated and adjusted in view of these new insights. Conclusions: This multidisciplinary treatment guideline may help involved therapists and physicians in the treatment of trigger finger and indicate areas needing additional research.